Effect Of Mifepristone on Serum Progesterone Level and Modified Bishop Score in Induction of Labour at A Tertiary Care Centre in Bihar - Shweta, Shweta; Ranjana, Ranjana; Goel, Neeru (Journal of Neonatal Surgery, 2025)
Background: Induction of labour is a pivotal intervention in obstetric practice, aimed at facilitating a safe and timely vaginal delivery. A favourable or "ripe" cervix is a fundamental prerequisite for its success. The present study aimed to evaluate the efficacy of oral mifepristone in inducing labour by examining its effect on cervical ripening, as measured by changes in the Modified Bishop’s score, and its impact on serum progesterone levels. Materials and Methods: This was a case-control study conducted at the Department of Obstetrics and Gynaecology at Indira Gandhi Institute of Medical Sciences, Patna, Bihar (India), for a duration of 1.5 years. A total of 220 participants fulfilling the inclusion criteria were divided into 2 groups: Group A (Case) with Bishop’s score <3 received 200 mg oral mifepristone and Group B (control) presented with spontaneous labour pain with cervical dilatation <3 cm. Change in Modified Bishop’s score and serum Progesterone levels were assessed 48 hours after administering Mifepristone or at the onset of established labour in Group A. In Group B, Modified Bishop’s score and serum progesterone measurement were done at the time of admission. Both groups were compared in terms of change in serum progesterone levels, number of patient’s went into active labour, mode of deliveries, indications of LSCS, and neonatal outcomes. Results: In the case group, mean Bishop Score significantly increased from 2.98 at the time of admission to 6.69 at 48 hours or onset of labor (p < 0.001), and the mean (SD) change in serum progesterone at 48 hours or onset of labor was -28.02 (22.90) ng/mL. There was a significant difference between the two groups in terms of serum progesterone level (48 hours/onset of labour) (t=-3.946, p=<0.001), with the mean serum progesterone level being highest in the control group. There was no significant difference between the 2 groups in terms of the number of patients who went into active labour, mode of deliveries, Indications of LSCS, and neonatal outcomes. Conclusion: Mifepristone significantly enhances cervical ripening as evidenced by significant changes in Bishop scores, and lowers serum progesterone levels in a clinically relevant timeframe and shortened labor intervals without increasing maternal or neonatal risk. Hence, mifepristone is a valuable adjunct in obstetric practice, especially for women requiring cervical ripening and induction of labor..